2016
DOI: 10.1016/j.pneurobio.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapies for neurobehavioral and cognitive recovery after experimental traumatic brain injury: Is more better?

Abstract: Traumatic brain injury (TBI) is a significant health care crisis that affects two million individuals in the United Sates alone and over ten million worldwide each year. While numerous monotherapies have been evaluated and shown to be beneficial at the bench, similar results have not translated to the clinic. One reason for the lack of successful translation may be due to the fact that TBI is a heterogeneous disease that affects multiple mechanisms, thus requiring a therapeutic approach that can act on complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 283 publications
4
64
0
Order By: Relevance
“…The lack of additive effects with the combinational therapy in adult TBI rats is not entirely surprising as several studies from our laboratory have shown similar effects. 11,52,64,74,76 Importantly, the combination of therapies did not produce negative effects as has been seen with different treatment paradigms. 64 The findings of the current study, and those previously reported, may be due to a floor effect.…”
Section: Journal Of Neurotraumamentioning
confidence: 71%
See 4 more Smart Citations
“…The lack of additive effects with the combinational therapy in adult TBI rats is not entirely surprising as several studies from our laboratory have shown similar effects. 11,52,64,74,76 Importantly, the combination of therapies did not produce negative effects as has been seen with different treatment paradigms. 64 The findings of the current study, and those previously reported, may be due to a floor effect.…”
Section: Journal Of Neurotraumamentioning
confidence: 71%
“…Indeed, several studies have shown negative interactions with combination therapies. 64 However, given that the decrease in behavioral outcome was only observed in gross motor function and not the more sensitive cognitive assay suggests that the effect may be due to behavioral variability vs. actual negative synergistic effects.…”
Section: Journal Of Neurotraumamentioning
confidence: 99%
See 3 more Smart Citations